2019
DOI: 10.1002/jbm4.10216
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bisphosphonates on Function and Mobility Among Children With Osteogenesis Imperfecta: A Systematic Review

Abstract: Osteogenesis imperfecta (OI) is a rare genetic connective tissue disorder that results in bone fragility and deformity. Management is multi‐disciplinary. Although pharmacologic intervention with bisphosphonates (BP) is a standard of care for individuals with severe OI, no consensus or reviews were found that focus on the effects of bisphosphonates on function and mobility. PubMed, CINAHL, Cochrane Library, Web of Science, and PEDro databases were searched for eligible articles for this review. Methodological q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…Some studies have postulated that use of bisphosphonates could facilitate a rodding surgical procedure 11 , 13 , 14 , 39 and benefit mobility, muscle force, and well-being 40 , 41 , and other studies found no changes in mobility 19 , 42 , 43 . A recent systematic review concluded that children given intravenous bisphosphonates have increased mobility 44 . However, in this study, we found no correlation between the use of bisphosphonates and mobility outcomes in the rodded group.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have postulated that use of bisphosphonates could facilitate a rodding surgical procedure 11 , 13 , 14 , 39 and benefit mobility, muscle force, and well-being 40 , 41 , and other studies found no changes in mobility 19 , 42 , 43 . A recent systematic review concluded that children given intravenous bisphosphonates have increased mobility 44 . However, in this study, we found no correlation between the use of bisphosphonates and mobility outcomes in the rodded group.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with osteogenesis imperfecta suffer from brittle bones, joint hyperlaxity, and a number of different soft tissue defects [9]. Bisphosphonates remain the mainstay of medical treatment for these patients [10][11][12]. e orthopaedic surgical management utilizing intramedullary fixation to treat long bone deformity and prevent future fractures has been thoroughly described and has demonstrated successful long-term clinical and radiographic outcomes [1,3,5,13].…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates are used to reduce bone resorption and increase bone mineral density. The effect of bisphosphonates in OI has been debated, and according to a recent systematic review, randomized controlled trials did not demonstrate a significant improvement in function and mobility with oral bisphosphonate administration, whereas nonrandomized open-label uncontrolled studies demonstrate that oral and intravenous bisphosphonate administration objectively improved function and mobility [ 9 ].…”
Section: Osteogenesis Imperfectamentioning
confidence: 99%